Seismic performance of steel frames with a hybrid bracing system combining concentric steel bracing and friction dampers (Fracture and Structural Integrity, 2026)
This paper assesses a hybrid bracing system involving concentric steel bracing in combination with friction dampers to improve seismic performance in steel moment frame buildings. Three prototype (5, 10, and 15 stories) steel moment frame configurations were analyzed under a nonlinear time history and pushover sequences as per performance-based design procedure, to examine the effects of the without, brace-only, damper-only, and hybrid systems. The hybrid system is most effective in decreasing roof displacement and story drift for all height configurations, with the maximum drift reductions of approximately 59% for the base brace system in the 5-story frame, while maintaining the optimal reductions of 15% - 31% (displacement) and 40% - 48% (drift) in 10- and 15-story frames. The hybrid method, unlike a brace-only solution, which can intensify the response of a tall structure through shortening of the periods of the oscillation and resonance, and damper-only solution, which lacks a stiffness control, is composed of both: initial stiffness and stable frictional energy dissipation. For taller frames, damping due to the vertical difference in load and slip should be taken into account, and then the suspension distribution should be adjusted to account for these higher mode effects.
Keywords: ETABS; Earthquakes; Damper; Steel braces; Pushover